Peningkatan hasil belajar bolavoli dengan menggunakan sistem daring - Supriyadi, Andi; Dupri (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2020)
This study aims to determine the improvement of volleyball learning outcomes using the online system in class XII MIPA 2 MA Madinatun Najah Rengat. This research is a classroom action research, which is to determine the improvement of learning outcomes for volleyball using an online system. The subjects of this study were 27 students of class XII MIPA 2 MA Madinatun Najah Rengat. The value taking is cognitive using volleyball material tests or quizzes. The results showed that in cycle I there were 26 students who completed with a percentage of 96% and 1 student who did not complete it with a percentage of 4%, in the second cycle there were 27 students with a percentage of 100% and no one who did not complete. Based on the results of the research, it can be concluded that using online learning systems can improve volleyball learning outcomes in class XII MIPA 2 MA Madinatun Najah Rengat. It is hoped that this online system can be a solution for physical education teachers in teaching during the Covid 19 pandemic.